Pengaruh Corporate Governance terhadap Keputusan Investasi - Maria Gorethi Berek; Elok Pakaryaningsih (Jurnal Riset Manajemen dan Bisnis, 2009)
The objective of this research is to examine the effect of corporate governance mechanism on investment decision. Using two ways of measurement, namely, board size and institutional ownership, corporate governance is hypothesized to have an effect oninvestment decision in which measured by asset growth, equity growth and debt growth.Using real estate industry listed at Jakarta Stock Exchange as the sample, the result shows that both institutional ownership and board size do not affect investment decision.Keywords: Corporate governance, investment decision, institutional ownership, board size